Nothing is Impossible : The Real-Life Adventures of a Street Magician - Dynamo (London Ebury Press, 2012)
When you're a kid life can seem tough; tougher for some than others. But the darkest of times can also be the most enlightening. When his late granddad showed him magic for the first time, Steven Frayne knew there was more to life than hiding from bullies.
Include Illustrations.
The Real-Life Adventures of a Street Magician.
Keywords: Magicians -- Great Britain